2017
DOI: 10.1007/s00484-017-1379-0
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of temperature and humidity on the symptoms of COPD patients

Abstract: This panel study investigates how temperature, humidity, and their interaction affect chronic obstructive pulmonary disease (COPD) patients' self-reported symptoms. One hundred and six COPD patients from Shanghai, China, were enrolled, and age, smoking status, St. George Respiratory Questionnaire (SGRQ) score, and lung function index were recorded at baseline. The participants were asked to record their indoor temperature, humidity, and symptoms on diary cards between January 2011 and June 2012. Altogether, 82… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…As to YLL for specific diseases, the effects of cold and heat on the CV system are stronger than those on the respiratory system. This might have led to a higher YLL attributable to CV mortality in this study, consistent with other studies [42,43]. Exposure to cold increases numbers of erythrocytes and blood platelets and leads to an increase of blood cholesterol and fibrinogen [44,45], which contributes to CV diseases.…”
Section: Discussionsupporting
confidence: 90%
“…As to YLL for specific diseases, the effects of cold and heat on the CV system are stronger than those on the respiratory system. This might have led to a higher YLL attributable to CV mortality in this study, consistent with other studies [42,43]. Exposure to cold increases numbers of erythrocytes and blood platelets and leads to an increase of blood cholesterol and fibrinogen [44,45], which contributes to CV diseases.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, it is very important to pay attention to the quality of that indoor air, temperature, humidity, and pressure, especially as COPD patients must live in a safe environment, away from any kind of irritants. Based on the outcomes of a wide range of studies [35][36][37][38][39][40][41][42][43][44][45][46][47] that addressed internal environmental conditions, we were able to draw up safe limits for all indoor climate factors. The foundations of internal protection have been translated into a hierarchical tree, as shown in Figure 4.…”
Section: Indoor Rulesmentioning
confidence: 99%
“…This study demonstrated that the optimal respiratory recordings were obtained at and above 21 • C in the living room and at least 9 h at 18 • C in the bedroom during the night. Mu et al [36] found that indoor temperature should be kept to an average of 18.2 • C. The WHO's annual world health statistics report recommends that for certain groups such as people over the age of 65, the minimum indoor warmth threshold is 20 • C, but there is no evidence that these findings are applicable to chronic pulmonary diseases [37,38]. The COPD Foundation's Slim Skinny Reference Guide (SSRG) [39] and Excellus BlueCross BlueShield [40] suggested keeping the indoor humidity below 40% and above 30%, respectively, to avoid harmful influences.…”
Section: Indoor Rulesmentioning
confidence: 99%
“…This region has a high rate of precipitation and humidity and has a large area of forestation that affects the number of pollens, and we recommend carrying out further studies to investigate this issue. Humidity and high temperatures are directly related to the worsening of symptoms in COPD patients whereas high humidity and low temperatures are shown to increase the risk of developing COPD (27). The lowest percentage of prevalence of hospitalization is in the Marmara Region (0.34%).…”
Section: Discussionmentioning
confidence: 99%